1991
DOI: 10.3379/jmsjmag.15.s1_351
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Design of Magneto-Optical Disk Structure

Abstract: Accurate servo-signal, good recording characteristics and sufficient signal-to-noise ratio are revealed to be necessary conditions for the optimum design of magneto-optical (MO) disks.' These conditions are dependent on the characteristics of the disk drive. This paper focuses on digital MO disks with a diameter of 130 mm which conform to the ISO standard. E-polarized incident light where the electric vector is parallel to the grooves is suitable for obtaining a stable servo signal and Hpolarized light where t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Several studies have reported that the MOKE can be enhanced by using a dielectric thin film on the surface of a magnetic material. [13][14][15][16] Theoretical studies on the MOKE in multiple layer materials were performed. 13,[16][17][18][19] Nowadays, MOKE enhancement is studied using nanometerscale microstructures, 20) optical cavities, [21][22][23][24] and confined light by plasmons for electromagnetic enhancements.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that the MOKE can be enhanced by using a dielectric thin film on the surface of a magnetic material. [13][14][15][16] Theoretical studies on the MOKE in multiple layer materials were performed. 13,[16][17][18][19] Nowadays, MOKE enhancement is studied using nanometerscale microstructures, 20) optical cavities, [21][22][23][24] and confined light by plasmons for electromagnetic enhancements.…”
Section: Introductionmentioning
confidence: 99%